Sociology and Anthropology: An emerging field of study in Nepal - Gurung, Om (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1064 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.4-12